2010
DOI: 10.1182/blood-2010-03-274704
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of the TET2 gene in 355 MDS and CMML patients reveals low-abundance mutant clones with early origins, but indicates no definite prognostic value

Abstract: Mutations in the TET2 gene are frequent in myeloid disease, although their biologic and prognostic significance remains unclear. We analyzed 355 patients with myelodysplastic syndromes using "next-generation" sequencing for TET2 aberrations, 91 of whom were also subjected to single-nucleotide polymorphism 6.0 array karyotyping. Seventy-one TET2 mutations, with a relative mutation abundance (RMA) > 10%, were identified in 39 of 320 (12%) myelodysplastic syndrome and 16 of 35 (46%) chroni myelomonocytic leukemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
174
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(185 citation statements)
references
References 30 publications
8
174
1
2
Order By: Relevance
“…28 TET2 mutations are the most common genetic abnormality found in chronic myelomonocytic leukemia, being present in around 40% cases. 29,30 Although TET2 mutations can represent early molecular events in myeloproliferative neoplasms, in a recent study of JAK2 mutation-positive myeloproliferative neoplasms based on colony assays, genotyping for TET2 and JAK2 mutations, it was demonstrated that TET2 can be a late event in the progression of myeloproliferative neoplasms and may represent an acquired abnormality in a separate (JAK2 mutation-negative) clone. 31 It is intriguing to speculate that the acquisition of KRAS, TET2 or other mutagenic events could have played a role in the phenotypic shift observed in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…28 TET2 mutations are the most common genetic abnormality found in chronic myelomonocytic leukemia, being present in around 40% cases. 29,30 Although TET2 mutations can represent early molecular events in myeloproliferative neoplasms, in a recent study of JAK2 mutation-positive myeloproliferative neoplasms based on colony assays, genotyping for TET2 and JAK2 mutations, it was demonstrated that TET2 can be a late event in the progression of myeloproliferative neoplasms and may represent an acquired abnormality in a separate (JAK2 mutation-negative) clone. 31 It is intriguing to speculate that the acquisition of KRAS, TET2 or other mutagenic events could have played a role in the phenotypic shift observed in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients had deletions in 4q removing the entire TET2 gene. Although TET2 was identified as the most frequently mutated gene in MDS, [18][19][20] its role in disease remains controversial; two reports describe no impact of TET2 mutations on survival in MDS/MPD (myeloproliferative disease), 18,21 another describes an association with decreased overall survival in AML 13 and, most recently, TET2 mutations were reported to be an independent favorable prognostic factor in MDS. 22 Two patients had submicroscopic deletions in 5q; one was only 1.35 Mb in 5q31.2, affecting the more proximal AML/MDS region.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It has become apparent that NGS platforms will have practical applications in clinical diagnostics and applications, such as detection of EGFR mutations in lung adenocarcinoma, 3 characterizing RAS and methylation pathway alterations in myeloproliferative diseases and myeloid leukemias, [4][5][6][7] or high-resolution, high-throughput human leukocyte antigen genotyping have been developed. 8,9 Thus far, limited data are available on the technical performance of amplicon deep sequencing in a clinical diagnostic setting.…”
Section: Introductionmentioning
confidence: 99%